Builders, tenants, and squatters: the origins of genetic material in modern stromatolites. Issue 3 (1st February 2021) - Petryshyn, Victoria A.; Junkins, Emily N.; Stamps, Blake W.; Bailey, Jake V.; Stevenson, Bradley S.; Spear, John R.; Corsetti, Frank A.
Abstract: Micro‐organisms have long been implicated in the construction of stromatolites. Yet, establishing a microbial role in modern stromatolite growth via molecular analysis is not always straightforward because DNA in stromatolites can have multiple origins. For example, the genomic material could represent the microbes responsible for the construction of the stromatolite (i.e., "builders"), microbes that inhabited the structure after it was built (i.e., "tenants"), or microbes/organic matter that were passively incorporated after construction from the water column or later diagenetic fluids (i.e., "squatters"). Disentangling the role of micro‐organisms in stromatolite construction, already difficult in modern systems, becomes more difficult as organic signatures degrade, and their context is obscured. To evaluate our ability to accurately decipher the role of micro‐organisms in stromatolite formation in geologically recent settings, 16/18S SSU rRNA gene sequences were analyzed from three systems where the context of growth was well understood: (a) an actively growing stromatolite from a silicic hot spring in Yellowstone National Park, Wyoming, where the construction of the structure is controlled by cyanobacteria; (b) a mixed carbonate and silica precipitate from Little Hot Creek, a hot spring in the Long Valley Caldera of California that has both abiogenic and biogenic components to accretion; and (c) a near‐modern lacustrine carbonate stromatolite from Walker Lake, Nevada that is likely abiogenic. In all cases, the largest percentage of recovered DNA sequences, especially when focused on the deeper portions of the structures, belonged to either the tenant or squatter communities, not the actual builders. Once removed from their environmental context, correct interpretation of biology's role in stromatolite morphogenesis was difficult. Because high‐throughput genomic analysis may easily lead to incorrect assumptions even in these modern and near‐modern structures, caution must be exercised when interpreting micro‐organismal involvement in the construction of accretionary structures throughout the rock record.